Multivariate Statistical Approach to Identify Heavy Metal Sources in Urban Roadside Soils of Manisa, Turkey - GURHAN YALCIN, M.; UNAL, BUNYAMIN (Asian Journal of Chemistry, 2010)
The aim of this study was to investigate heavy metal pollution in roadside soils of Manisa, an important city located in the western part of Turkey. Soil samples were collected from roadsides of the city. Heavy metal concentrations were measured with Spectro-Xepos Benchtop X-Ray fluorescence spectrometer. Mean heavy metal concentrations (ppm) of the roadside soils in Manisa were as follows: Sb was 7.56, W 6.19, Ag 5.8, Mo 22.1, Co 28.37, V 94.0, Cu 136.57, As 26.95, Sn 19.99, Hg 1.71, Ni 64.67, Zn 126.19, Cd 4.05, Pb 47.97, Al 58730, Fe 34515, Mg 13841, Cl 350.76, Ti 3857.5, Cr 341.83 and Mn 704.3. Based on the chemical analyses, Ag, Cd, Fe, Al, Mo, Hg, Sb, Cr, W, Sn, Cu, As, Pb, Cl, Co and Zn concentrations of roadside soils in Manisa were higher than those of the earth's crust and North European soil. Results of the chemical analyses were evaluated with multivariate statistics with high accuracy rates. Heavy metal pollution of the roadside soils in Manisa can be attributed to highways and industrial and household wastes. It can be suggested that traffic on the busy highways along schools, hospitals and playgrounds for children should be diverted in the short term and such institutions should be built away from the highways and industrial areas in the long term.